Implementation of the Naïve Bayes Algorithm for Divorce Prediction at the Tais Religious Court - Windarman Windarman; Sapri Sapri; Eko Suryana (Penerbit Jurnal Indonesia, 2022)
Divorce is the breaking up of a husband and wife relationship, because there is no match between the two. Divorce is basically the release of the bond between husband and wife. In Tais district, based on the Tais Religious Court Annual Report from 2017, 2018 and 2019 it was found that there was an increase in the divorce rate. Based on the divorce rate which continues to increase every year, it is necessary to have data in the form of data to determine the factors that influence divorce. The use of Naive Bayes is that this method only requires a small amount of training data (Training Data) to determine the parameter estimates needed in the prediction process. In this case, it is assumed that the presence or absence of a certain event from a group is not related to the presence or absence of other events. With a system to predict divorce, it can help users who want to know the prediction of divorce. Based on the tests that have been carried out using the Black Box Method, the results show that the functionality of the divorce data prediction application has run as expected and the application is able to display the prediction results of Divorce Lawsuit and Divorce Divorce